Socio-economic factors influencing the adoption of solar home systems: the case study of Ghana - Emmanuel Effah; Samuel Gyamfi; Felix Amankwah Diawuo; Emmanuel Yeboah Asuamah (Scientific African)
This study examines the socio-economic factors influencing the adoption and utilisation of Solar Home Systems (SHSs) in remote communities of Ghana. Using a mixed-methods approach, the research incorporates household surveys of SHS users and non-users, along with in-depth interviews with key stakeholders in the SHS industry. The findings reveal that access to finance, education level, and awareness of SHS benefits are key determinants of adoption. Additionally, the availability of government subsidies and microfinance institutions significantly enhances SHS uptake.Despite the advantages of SHSs, the study finds that they are not a primary driver for establishing Home-Based Businesses in rural communities. However, they have contributed to a 3.81 % increase in household savings and improved the operational conditions of existing businesses. Moreover, 41.59 % of respondents reported enhanced nighttime security, while 28 % noted an extension in study hours for children due to improved lighting.The study concludes that targeted policy interventions addressing financial accessibility, community engagement, and infrastructure support are essential for maximising the socio-economic benefits of SHSs. Expanding SHS adoption in developing countries can significantly improve energy access, quality of life, and rural economic resilience.